2013
DOI: 10.5937/gads1348049z
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the body mass index in development of osteoporosis

Abstract: ¹Specijalna bolnica za reumatske bolesti Novi Sad,²Dom zdravlja "Novi Sad" Novi Sad,³Klinika za ortopediju i traumatologiju Novi Sad, Klinički centar Vojvodine, 4 Dom zdravlja Žitište Sažetak UVOD: Osteoporozu odlikuje smanjena mineralna koštana gustina (BMD), povećana fragilnost i sklonost ka prelomima. Veliki uticaj u nastanku osteoporoze imaju i faktori rizika među koje spada nizak indeks telesne mase (BMI). CILJ: Utvrditi značaj indeksa telesne mase u nastanku osteoporoze. MATERIJAL I METOD: Prospektivno i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
2
1
0
Order By: Relevance
“…The statistically significant association between the BMI and the T-score of the hip, as well as the T-score of the spine that was identified in our study is also confirmed in the research of Zvekić-Svorcan et al [20], showing that there is a relationship between persons' BMI and their lumbar spine and hip T-scores i.e. there is association between the decreased BMD and the low BMI [20]. Kang et al [21] found that the hip bone strength deteriorated with aging and enhanced with higher BMI and longer time of years of menstruation in Chinese postmenopausal women.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The statistically significant association between the BMI and the T-score of the hip, as well as the T-score of the spine that was identified in our study is also confirmed in the research of Zvekić-Svorcan et al [20], showing that there is a relationship between persons' BMI and their lumbar spine and hip T-scores i.e. there is association between the decreased BMD and the low BMI [20]. Kang et al [21] found that the hip bone strength deteriorated with aging and enhanced with higher BMI and longer time of years of menstruation in Chinese postmenopausal women.…”
Section: Resultssupporting
confidence: 91%
“…In our research, none of the female respondents had BMI value ˂18,5 kg/m 2 . The statistically significant association between the BMI and the T-score of the hip, as well as the T-score of the spine that was identified in our study is also confirmed in the research of Zvekić-Svorcan et al [20], showing that there is a relationship between persons' BMI and their lumbar spine and hip T-scores i.e. there is association between the decreased BMD and the low BMI [20].…”
Section: Resultssupporting
confidence: 89%
“…Aerobic exercise can be successfully used to regulate the percentage of fat in the organism, due to which BW and BMI were also monitored in this study. Some researches 35,36 show that thinner women with BMI lower than 19 kg/m 2 are at a higher risk of osteoporosis. Persons with higher BW also have higher BMD and are at a lower risk of osteoporosis 37,38 .…”
Section: Discussionmentioning
confidence: 99%